Potencial Social Conflict in Palm Oil Plantation Area and Alternative Solutions in Sambas Regency - Mustarini Dessy Vitiara; Herdis Herdiansyah; Evi Frimawaty (Jurnal Ilmu Sosial dan Humaniora, 2024)
The presence of a palm oil company in an area can be a mainstay in the economic sector, providing employment opportunities and indirect benefits from local infrastructure development. In other conditions, environmental damage and social conflict challenges emerge as risks from palm oil company activities. This study aims to analyze the positive and negative impacts of oil palm according to society, the social conflicts it causes because of environmental damage, and provide alternative solutions. For the objectives to be answered, a qualitative approach was used to gather a purposive sampling of informants with data collected from local communities near plantations (primary) and documentation (secondary). One hundred and one questionnaires were distributed, and interviews were conducted between 12 and 28 November 2023. It found that oil palm plantations boost local economies by facilitating easier sales of small-scale farmers' harvests to companies at stable prices, ensuring steady income, especially when prices are high. Infrastructure improvements, such as road paving and bridge construction funded by CSR initiatives, benefit the community despite some road damage from plantation vehicles. However, plantations are causing environmental damage, creating economic inequality, and disrupting traditional communities. Expansion leads to social jealousy, cultural loss among Indigenous people, and road damage from plantation traffic; worse still, it causes conflicts between the community and the company. In addressing social conflicts, communities have engaged in environmental conservation through cooperation, customary deliberations, and dialogues with companies and the government. Therefore, social approaches are highly effective as alternative solutions for resolving social conflicts.